Global Maps of Equatorial Plasma Bubbles Depletions Based on FORMOSAT‐7/COSMIC‐2 Ion Velocity Meter Plasma Density Observations - Irina Zakharenkova; Iurii Cherniak; John J. Braun; Qian Wu (Space Weather)
Abstract FORMOSAT‐7/COSMIC‐2 is the largest equatorial multi‐satellite constellation of six full‐size satellites to study the equatorial ionosphere. Each satellite is equipped by an ion velocity meter (IVM) instrument to provide high rate in situ plasma density observations along the low‐inclined satellite orbits at ∼530–550 km altitude. Six satellites provide an unprecedented dense coverage of the entire equatorial region around the globe and allow reliable detection of equatorial plasma bubbles (EPBs) and plasma density irregularities at different local times/longitudinal sectors simultaneously. We present a method for detection of EPBs in FORMOSAT‐7/COSMIC‐2 in situ plasma density data and construction of the global maps of EPB geolocations. The results in the form of time series and IVM‐based global Bubble Maps have a great potential for both near real‐time monitoring of space weather conditions and long‐term statistical analysis of EPB occurrence in regional or global scales. We present first FORMOSAT‐7/COSMIC‐2 derived climatological characteristics of the post‐sunset and post‐midnight EPBs occurrence probability and their apex altitudes during a period of low solar activity. Also, we demonstrate the good performance of the FORMOSAT‐7/COSMIC‐2 IVM‐based Bubble Maps when compared to optical images and ground‐based ionosonde observations.